INFLUENCE OF SELF-ESTEEM AND SUBSTANCE USE ON DEPRESSION AMONG UNDERGRADUATE STUDENTS OF FEDERAL UNIVERSITY OF LAFIA, NASARAWA STATE, NIGERIA - Aliyu Abubakar, Suleiman; Shuaibu Umar, Shitu; Musa Tafida, Abubakar; Tijjani Usman, Ishaq; Ibrahim Joseph, Orume; Yusuf Agana, Kemi (African Journal of Social and Behavioural Sciences, 2024)
This study examines how self-esteem and substance use impact depression among undergraduates at the Federal University of Lafia, Nigeria. Three hundred and ninety (390) participants with ages ranging from 19-25 years (Mean= 18.779; SD=11.42) were selected using a simple random sampling technique. A survey research method was adopted for the study. Rosenberg’s self-esteem scale, Substance use questionnaire, and Beck’s depression inventory were used to collect data. Linear regression was used to analyse hypotheses one and two, and multiple regression was used to analyse hypothesis three. Findings indicated that self-esteem significantly influenced depression among undergraduate students of the Federal University of Lafia (R = 0.863 = R2 = 0.547 (F (1,389) = 192.192, t = 14.170, p < .05). Also, it shows that substance use significantly influenced depression among undergraduate students of Federal University of Lafia (R = 0.536 = R2 = 0.213 (F (1,389) = 63.820, t = 4.711, p < .05). Similarly, the results revealed that self-esteem and substance use jointly influenced depression among undergraduate students of Federal University of Lafia (R = 0.724 = R2 = .520 (F (2, 388) = 107.544, t = -5.087, p < .05). It was recommended that; University management should ensure the availability of mental health resources and support services for students. This could include counselling services, workshops on self-esteem management and well-being, and access to mental health professionals. There should be regular assessment of the mental health and well-being of students through surveys or confidential feedback mechanisms. This can help identify individuals who may be at risk of depression and enable targeted interventions or support. Substance use tests should be done regularly in order to checkmate the illegal use of substances by students.